2017
DOI: 10.1159/000484120
|View full text |Cite
|
Sign up to set email alerts
|

Aloe-Emodin Relieves High-Fat Diet Induced QT Prolongation via MiR-1 Inhibition and IK1 Up-Regulation in Rats

Abstract: Background/Aims: High-fat diet (HFD) causes cardiac electrical remodeling and increases the risk of ventricular arrhythmias. Aloe-emodin (AE) is an anthraquinone component isolated from rhubarb and has a similar chemical structure with emodin. The protective effect of emodin against cardiac diseases has been reported in the literature. However, the cardioprotective property of AE is still unknown. The present study investigated the effect of AE on HFD-induced QT prolongation in rats. Methods: Adult male Wistar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…Compared with those in the ND group, the LDL, TG and TC circulatory levels were significantly higher in the HFD group (Supplementary Figure 1). Interestingly, 6-week treatment of AE reversed the hyperlipidemia and AE reduced LDL, TG, and TC circulatory levels induced by HFD, consistent with our previous study [17]. Increased inflammatory infiltration is one of the hallmarks of the progression of inflammation; hematoxylin-eosin staining validated our guess.…”
Section: Ae Reduces Myocardial Inflammatory Injury In Hfdsupporting
confidence: 91%
See 1 more Smart Citation
“…Compared with those in the ND group, the LDL, TG and TC circulatory levels were significantly higher in the HFD group (Supplementary Figure 1). Interestingly, 6-week treatment of AE reversed the hyperlipidemia and AE reduced LDL, TG, and TC circulatory levels induced by HFD, consistent with our previous study [17]. Increased inflammatory infiltration is one of the hallmarks of the progression of inflammation; hematoxylin-eosin staining validated our guess.…”
Section: Ae Reduces Myocardial Inflammatory Injury In Hfdsupporting
confidence: 91%
“…As a member of the anthraquinone family, AE occurs in the leaves of aloe and exhibits a variety of pharmacological properties, such as antibacterial, anticancer, and antioxidant activities. Recently, AE has been reported to have antiinflammatory effects [16]; in addition, AE previously showed a lipid-lowering effect in vivo [17]. However, the effect of AE on hyperlipidemia-induced cardiac inflammation has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In the present research, single-cell recordings showed that APD 20 , APD 50 , and APD 90 were markedly prolonged in WT-HFD mice compared with WT-ND mice. Our result is in agreement with a previous work by Bai and coworkers in myocytes isolated from HFD-fed rat hearts [18]. In their experiments, APD 90 was markedly elongated by HFD.…”
Section: Discussionsupporting
confidence: 94%
“…33 Previous studies have indicated that Rhubarb has a promising protective effect against lung and renal fibrosis. 34,35 AE is an active compound in the plant rhubarb, 36 which is a traditional medicine used widely in the treatment of a variety of diseases in China. 37 Our study showed for the first time that AE protected against renal injury in a UUO model.…”
Section: Discussionmentioning
confidence: 99%